Ozone and temperature on 'Roxinho of Kenya' passion fruit bioactive compounds during storage - Maia Nunes, Kelly Nazare [UNESP]; Silva Ripardo, Ana Karolina da; Goto, Rumy [UNESP]; Minatel, Igor Otavio [UNESP]; Pereira Lima, Giuseppina Pace [UNESP] (Univ Federal Rural Pernambuco, 2018)
Several alternative methods for fruit sanitization have been studied to extend the post-harvest life. Here we investigated whether the sanitization with ozone influences the content of some bioactive compounds during 'Roxinho of Kenya' passion fruit post-harvest. The fruit were immersed in ozonated water, stored at room temperature or under refrigeration for 30 days. Total carotenoids, total phenols, total flavonoids, ascorbic acid, and antioxidant activity in fruit pulp were analyzed. Ozone sanitization did not influenced in the total carotenoids content of fruits stored at room temperature or after immersion for 10 min. in ozonated water and stored in a cold chamber. Sanitization had no influence on total phenol or flavonoid content until day 10 of storage at both temperatures. There was no definite tendency of the ozone action in the ascorbic acid levels or antioxidant activity. There was no microbiological contamination during the storage. The ozone combined with room temperature was unable to maintain the passion fruit post-harvest life and quality. The best conservation method to retain the bioactive levels in 'Roxinho of Kenya' passion fruit is the combination of ozone sanitization for 5 min. and stored in cold chamber for 10 days.
Keywords: antioxidants; Passiflora edulis; phenolic compounds; sanitization; soluble solids; titratable acidity